The Role of Sibaliparri Harmonization in Promoting Blue Economy Practices among Fisherman in West Sulawesi - Nurwahyuni Syahrir; Arlistria Muthmainnah; Puspa Dewangga (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose – This study aims to examine the role of Sibaliparri harmonization in promoting blue economy practices in the financial management of fishing households in West Sulawesi. Method - This study is a mixed-method study witn an embedded model to analyze quantitatively and qualitatively. Main Findings - The results of this study indicate that attitudes and internalization of Sibaliparriq cultural values are the main determinants of fishermen's intentions to adopt blue economy practices in household financial management. The empirical findings are in line with the theory of planned behavior, which places attitudes and subjective cultural norms as the main sources of intention to behave positively, even though government policies have not yet shown an influence on fishermen's intentions to implement blue economy practices. Theory and Practical Implications - The findings of this study serve as a reference for the government in formulating policies to raise awareness of blue economy practices among fishermen. Future research could focus on identifying government obstacles in implementing policies related to blue economy practices. Novelty - his study integrates economic, social, and environmental perspectives that focus on the behavior of local communities, in this case fishermen.